Antibacterial hydroxyapatite fiber-gelatin composite scaffold as well as preparation method and application thereof

By preparing an antibacterial hydroxyapatite fiber and gelatin composite scaffold, the problems of insufficient mechanical stability, pore structure and antibacterial properties of existing scaffolds were solved, and the mechanical properties and antibacterial properties of the scaffold were improved. It provides a biomimetic cancellous bone microenvironment and is suitable for rapid repair of infected bone defects.

CN121288022APending Publication Date: 2026-01-09SHANDONG FIRST MEDICAL UNIV & SHANDONG ACADEMY OF MEDICAL SCI +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511867500.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-11
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing bone tissue engineering scaffolds have limitations in terms of antibacterial function, material system, structural design and biomimetic performance, making it difficult to meet the clinical needs of repairing infected bone defects, especially in terms of mechanical stability, pore structure and antibacterial properties.

Method used

An antibacterial hydroxyapatite fiber and gelatin composite were used to prepare an interwoven composite scaffold through thermo-cold phase separation and paraffin ball template leaching technology. This formed a porous fibrous network structure with regular spherical macropores and interconnected pores, which combined with metal ions such as copper, silver and cerium ions to achieve antibacterial and promote bone differentiation.

Benefits of technology

It achieves improved mechanical properties of the scaffold, possesses good antibacterial and biocompatibility, provides a biomimetic cancellous bone microenvironment, promotes new bone formation and blood vessel ingrowth, and is suitable for rapid repair of infected bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121288022A_ABST
    Figure CN121288022A_ABST
Patent Text Reader

Abstract

The invention discloses an antibacterial hydroxyapatite fiber-gelatin composite scaffold as well as a preparation method and application thereof, the composite scaffold has the structural characteristics of regular spherical macropores and communicating pores, and the interior of the composite scaffold is formed by mutually interwoven antibacterial hydroxyapatite fiber-gelatin composite fibers; the preparation method comprises the following steps: injecting antibacterial hydroxyapatite fiber / gelatin turbid liquid into a paraffin ball template under negative pressure, and carrying out thermal cooling phase separation and a paraffin ball template leaching technology. The composite scaffold integrates multiple functions of active antibiosis, osteogenic differentiation promotion, neovascularization and bone tissue ingrowth and the like, and has huge application potential in the field of promotion of rapid repair and regeneration of infectious bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of biological materials, and particularly relates to an antibacterial hydroxyapatite fiber-gelatin composite scaffold as well as a preparation method and application thereof. BACKGROUND

[0002] The statements herein are provided only to enhance understanding of the general background of the present application and are not necessarily constituting the prior art.

[0003] Infectious bone defects are one of the difficult problems to be solved in the clinical field of orthopedics. With the aggravation of population aging, the continuous rise in the incidence of traumatic bone injury, and the significant increase in the demand for postoperative reconstruction of bone tumors, developing bone tissue engineering scaffolds with excellent biocompatibility, active antibacterial properties, biomimetic structural properties, and good osteogenic activity has become a key technical direction for addressing the challenge of repairing clinical infectious bone defects. An ideal bone tissue engineering scaffold needs to accurately simulate the physiological microenvironment of natural bone (especially cancellous bone) to provide a stable support carrier for cell adhesion, proliferation, and differentiation, while ensuring nutrient transport, metabolic waste discharge, and promoting the growth of new blood vessels and bone tissue, and ultimately achieving functional repair of bone defects. However, the existing bone tissue engineering scaffolds used in clinical applications still have certain limitations in terms of antibacterial function, material system, structural design, and biomimetic properties, making it difficult to fully meet the clinical needs.

[0004] The material system of the current clinical bone tissue engineering scaffolds is mostly single component or simple composite structure. For example, Gelfoam®, SURGISPON ® Although pure gelatin sponge scaffolds have good biocompatibility, they have very low mechanical strength and cannot provide long-term stable support. Porous hydroxyapatite bioceramics have high brittleness and degrade too slowly, leading to mismatch with the bone regeneration process. Even if gelatin or collagen is combined with hydroxyapatite, the existing products mostly use hydroxyapatite nanoparticles, which have limited mechanical enhancement effect. Prior patent CN115998958A provides a bone tissue engineering scaffold with a slow-release effect, which is composed of two dense layers on the outside and a loose porous layer in the middle. The dense layer is composed of hydroxyapatite fibers loaded with metal ions and gelatin, and the metal ions are preferably Sr ions to promote the bone formation process. The loose porous layer is composed of pure gelatin fibers and is also filled with growth factors to shorten the inflammation period. The outermost HA fiber / gelatin composite film prepared by the patent is a dense two-dimensional film, which simulates the cortical bone part and its main function is to prevent connective tissue and fibroblasts from invading the bone defect. The middle loose porous gelatin fiber layer simulates the cancellous bone part, and its main function is to provide attachment sites and growth space for mesenchymal stem cells. However, the overall mechanical stability of the scaffold structure is limited, and its osteogenic effect needs to be further improved.

[0005] In addition, the porous structure of the existing scaffold is mostly constructed by freeze-drying method or conventional poration technology (such as salt particle poration), which has two defects: on the one hand, it is difficult to prepare a regular porous network structure with uniform pore size and excellent connectivity; on the other hand, the control precision of porosity and pore size is low, which restricts the deep infiltration of cells, efficient transportation of nutrients and discharge of metabolic waste. More importantly, the above-mentioned scaffolds do not have active antibacterial function, and antibiotics such as penicillin and tetracycline are needed to prevent and control bacterial infection during and after operation, which cannot achieve long-term anti-infection effect during the repair period of infected bone defect.

[0006] In summary, there is no bone tissue engineering composite scaffold that can simultaneously meet the requirements of "active antibacterial function-bionic cancellous bone porous structure and composition" in the current clinical practice. SUMMARY

[0007] In view of the deficiencies of the prior art, the present application provides an antibacterial hydroxyapatite fiber-gel composite scaffold and a preparation method and application thereof. The composite scaffold prepared by the method has a bionic cancellous bone interconnected porous fibrous network structure and composition, the macroscopic pore size and connectivity are controllable, and it has multiple functions of antibacterial and promoting stem cell adhesion, osteogenic differentiation, and ingrowth of new blood vessels and bone tissue.

[0008] To achieve the above-mentioned purpose, the present application provides the following technical solutions: In a first aspect, the present application provides an antibacterial hydroxyapatite fiber-gel composite scaffold, comprising interwoven antibacterial hydroxyapatite fiber-gel composite fibers, the composite scaffold has the structural characteristics of regular spherical large pores and connected pores, and each spherical large pore has ≥1 connected pore. Wherein, the spherical large pore has a pore size of 200-800 μm, and the connected pore has a pore size of 80-120 μm; the antibacterial hydroxyapatite fiber-gel composite fiber has a diameter of 0.2-1.5 μm.

[0009] The antibacterial hydroxyapatite fiber-gel composite scaffold contains 10-25 wt.% of antibacterial hydroxyapatite fibers; in some embodiments of the present application, the balance is gelatin.

[0010] The antibacterial hydroxyapatite fiber-gel composite scaffold also contains metal ions selected from copper, silver and cerium ions. The content of the metal ions in the antibacterial hydroxyapatite fiber is 2-6 at.%.

[0011] In a second aspect, the present application provides a preparation method of the antibacterial hydroxyapatite fiber-gel composite scaffold of the first aspect. First, paraffin balls are stacked and heated to obtain a paraffin ball template; antibacterial hydroxyapatite fibers are mixed with a gelatin solution to obtain an antibacterial hydroxyapatite fiber / gelatin suspension; then the antibacterial hydroxyapatite fiber / gelatin suspension is injected into the paraffin ball template under negative pressure, and a non-crosslinked composite scaffold is obtained through thermally induced phase separation and paraffin ball template leaching technology; finally, the antibacterial hydroxyapatite fiber-gel composite scaffold is obtained through chemical crosslinking.

[0012] The antibacterial hydroxyapatite fibers are fibers doped with antibacterial ions, with a length of 50-500 μm and a diameter of 5-30 nm; the paraffin balls have a diameter of 200-800 μm, which determines the size of the scaffold spherical pore aperture; the paraffin ball template is obtained by stacking paraffin balls and heating at 30-45 ℃ for 10-60 min; the higher the heating temperature and the longer the heating time, the more the number of connected pores and the larger the pore size.

[0013] In some embodiments of the present application, the antibacterial hydroxyapatite fibers are prepared by a solvothermal method.

[0014] In some embodiments of the present application, the lower the temperature in the thermally induced phase separation process, the thinner the diameter of the composite fibers.

[0015] Specifically, the preparation method of the antibacterial hydroxyapatite fiber-gel composite scaffold provided by the present application comprises the following steps: S1, preparing a paraffin ball template; S2, preparing an antibacterial hydroxyapatite fiber / gelatin suspension; S3, injecting the antibacterial hydroxyapatite fiber / gelatin suspension obtained in step S2 into the paraffin ball template obtained in step S1 under negative pressure, and performing freeze-induced thermally induced phase separation; S4, removing the porogen paraffin by porogen leaching process to obtain an antibacterial hydroxyapatite fiber-gel composite scaffold which is not chemically crosslinked; S5, chemically crosslinking the antibacterial hydroxyapatite fiber-gel composite scaffold which is not chemically crosslinked obtained in step S4, washing, precooling, and freeze-drying to obtain an antibacterial hydroxyapatite-gel composite scaffold.

[0016] In the present application, the order of the material preparation processes of steps S1 and S2 is not limited.

[0017] In some embodiments of the present application, in step S1, the paraffin balls prepared by the microemulsion method are stacked and heated at 30-45 ℃ for 10-60 min to connect the paraffin balls to each other to form a paraffin ball template.

[0018] In some embodiments of the present application, in step S2, the following steps are included: S2.1, the antibacterial hydroxyapatite fibers are dispersed in a mixed solvent of water and ethanol under ultrasonic after hydrothermal washing, to obtain an antibacterial hydroxyapatite fiber slurry with a concentration of 0.005-0.1 g / mL; S2.2, gelatin is added to the slurry obtained in step S2.1, and stirred at 37-50 ℃ for 10-30 min to obtain an antibacterial hydroxyapatite fiber / gelatin suspension with a gelatin concentration of 0.01-0.2 g / mL.

[0019] In some embodiments of the present application, in step S3, the antibacterial hydroxyapatite fiber / gelatin suspension obtained in step S2 is injected into the template obtained in step S1 under negative pressure, and transferred to an environment of-80--20 ℃ for freezing for 3-18 h to induce the progress of the thermally induced phase separation process.

[0020] In some embodiments of the present application, in step S4, the following steps are included: S4.1, the product obtained in step S3 is soaked in anhydrous ethanol at-40--10 ℃ for 12-36 h, and then transferred into 1,4-dioxane for 12-36 h to remove ethanol and water in the product, and the 1,4-dioxane is replaced every 6-10 h; S4.2, the product obtained in step S4.1 is frozen at-18 ± 5 ℃ for 6-18 h, and freeze-dried for 12-36 h to remove 1,4-dioxane in the product; S4.3, the product obtained in step S4.2 is soaked in n-hexane for 12-36 h to completely remove the paraffin balls, and the n-hexane solvent is replaced every 2-8 h; S4.4, the product obtained in step S4.3 is soaked in a cyclohexane solution for 6-18 h to remove n-hexane, and the cyclohexane solvent is replaced every 1-6 h to obtain an antibacterial hydroxyapatite fiber-gelatin composite scaffold without chemical cross-linking; S4.5, the composite scaffold without chemical cross-linking obtained in step S4.4 is frozen at-18 ± 5 ℃ for 6-18 h, and freeze-dried for 12-36 h to remove cyclohexane in the product; S4.6, a morpholine ethanesulfonic acid buffer containing 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide is mixed with acetone according to a volume ratio of 20:80-5:95 to prepare a chemical cross-linking solvent; S4.7, the composite scaffold obtained in step S4.5 is soaked in the chemical cross-linking solvent obtained in step S4.6, and cross-linked at 0-10 ℃ for 12-36 h; S4.8, the composite scaffold of which the chemical cross-linking in step S4.7 is completed is washed, pre-cooled and freeze-dried to obtain the biomimetic cancellous bone antibacterial hydroxyapatite-gelatin composite scaffold.

[0021] The present application provides a preparation method different from the prior art: In the present application, the antibacterial hydroxyapatite fibers are washed by hydrothermal cleaning and ultrasonic dispersion to obtain a uniform slurry; then the gelatin is dissolved in the slurry to form a gelatin-fiber-solvent homogeneous dispersion system with the antibacterial hydroxyapatite fibers uniformly suspended, which lays a foundation for the uniform embedding of the fibers in the gelatin fiber matrix in the subsequent thermally induced phase separation process. In the thermally induced phase separation process, the gelatin begins to aggregate due to its thermal reversibility, driving the system to break through the thermodynamic equilibrium and spontaneously phase separate into two phases: one phase is a "polymer-rich phase" with gelatin molecules as the continuous phase and wrapping the antibacterial hydroxyapatite fibers through hydrogen bonding / electrostatic interaction, and the other phase is a "solvent-rich phase" mainly composed of water / ethanol, preliminarily forming a porous structure prototype with the antibacterial hydroxyapatite fibers uniformly embedded in the gelatin fiber matrix. Finally, the composite scaffold with the antibacterial hydroxyapatite fibers uniformly dispersed in the gelatin fiber matrix is obtained through solvent replacement and freeze-drying. In this structure, the antibacterial hydroxyapatite fibers and the gelatin fiber matrix form a stable interfacial bond, and when stressed, the stress can be uniformly transmitted to the rigid antibacterial hydroxyapatite fibers through the gelatin fiber matrix, realizing the synergistic bearing of the two materials and significantly improving the tensile strength, elastic modulus and fatigue resistance of the scaffold.

[0022] In some embodiments, in step S1, the diameter of the paraffin wax pellets is preferably 400-600 μm; further, the heating temperature is preferably 30-45 ℃, and the heating time is preferably 10-60 min. The higher the heating temperature and the longer the heating time, the more the number of interconnected pores formed inside the scaffold and the larger the pore size. Studies have shown that the scaffold with a large pore size of ~500 μm and interconnected pores of ~100 μm has the optimal biological and mechanical properties.

[0023] In some embodiments, in step S2, the antibacterial hydroxyapatite fibers are hydroxyapatite fibers doped with antibacterial ions selected from copper, silver and cerium ions; the content of the antibacterial ions is preferably 2-6 at.%.

[0024] In step S2.1, the concentration of the antibacterial hydroxyapatite fibers in the antibacterial hydroxyapatite fiber slurry is 0.0056-0.025 g / mL.

[0025] In step S2.1, the antibacterial hydroxyapatite fibers are prepared by a solvothermal method.

[0026] In step S2.1, the hydrothermal cleaning uses an ethanol / water solvent with a volume ratio of 10:1 to 1:1, a hydrothermal temperature of 60 to 90°C, and a hydrothermal time of 4 to 12 h. More preferably, the ethanol / water solution volume ratio is 6:1 to 3:1, the hydrothermal temperature is 65 to 75°C, and the hydrothermal time is 5 to 8 h. Hydrothermal treatment can reduce the oleate ions attached to the surface of antibacterial hydroxyapatite fibers, thereby improving the hydrophilicity and dispersibility of the fibers.

[0027] In step S2.1, the ultrasonic power is 100~500W and the ultrasonic time is 30~70 min. More preferably, the power is 300~400 W and the time is 45~55 min.

[0028] In step S2.2, the gelatin is bovine skin gelatin, bovine bone gelatin, or pigskin gelatin; the heating temperature is preferably 40~45 ℃, the stirring time is preferably 20~25 min, and the gelatin concentration is preferably 0.05~0.15 g / mL.

[0029] In step S3, the preferred injection volume of the suspension is 1.5~2 mL; the negative pressure is 500~1500 Pa, preferably 800~1300 Pa; the preferred freezing temperature is -60~-40 ℃; and the preferred freezing time is 6-12 h.

[0030] In step S4.1, the soaking time of the product in anhydrous ethanol is preferably 18-24 h, the soaking time of 1,4-dioxane is preferably 18-24 h, and the time interval for changing 1,4-dioxane is preferably 6-8 h.

[0031] In step S4.2, the freezing time of the product is preferably 10-15 h, the freeze-drying temperature is preferably -60~-40℃, and the freeze-drying time is preferably 24~30 h.

[0032] In step S4.3, the soaking time of the product in n-hexane is preferably 24-30 h, and the time interval for changing n-hexane is preferably 4-6 h.

[0033] In step S4.4, the soaking time of the product in cyclohexane is preferably 8 to 12 hours, and the time interval for changing the cyclohexane is preferably 2 to 4 hours.

[0034] In step S4.5, the freezing time is preferably 10~15 h, the freeze-drying temperature is preferably -60~-40 ℃, and the freeze-drying time is preferably 20~30 h.

[0035] In step S4.6, the concentration of the morpholine ethanesulfonic acid buffer is preferably 0.03~0.1 mol / L, pH = 5.3±0.1; the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the morpholine ethanesulfonic acid buffer is preferably 0.01~0.05 wt.%, and the mass ratio of the composite scaffold, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to N-hydroxysuccinimide is preferably (2~4):(1~2):(0.4~0.8); the volume ratio of the morpholine ethanesulfonic acid buffer containing 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide to acetone is preferably 10:90~5:95.

[0036] In step S4.7, the preferred chemical crosslinking temperature is 2~6 ℃, and the preferred chemical crosslinking time is 20~30 h.

[0037] In step S4.8, the washing is performed by alternating between deionized water and anhydrous ethanol; the pre-cooling temperature is preferably -20 to -10°C, the pre-cooling time is preferably 18 to 24 h, the freeze-drying temperature is preferably -60 to -40°C, and the freeze-drying time is preferably 24 to 36 h; the weight percentage of antibacterial hydroxyapatite fiber in the composite scaffold is preferably 10 to 25 wt.%.

[0038] Thirdly, the present invention provides an application of an antibacterial hydroxyapatite fiber-gelatin composite scaffold in the repair or regeneration of infected bone defects.

[0039] The composite scaffold provided by this invention has an interconnected porous fiber network structure, which can promote cell attachment, migration, and proliferation within the scaffold, facilitating the transport of nutrients and oxygen, the removal of metabolic waste, and the ingrowth of new bone tissue and blood vessels. Furthermore, the antibacterial hydroxyapatite fibers not only effectively enhance the mechanical strength of the scaffold, but the calcium and phosphate ions released during their degradation can also serve as ion sources for new bone formation. Simultaneously, the continuously released antibacterial ions, such as copper, silver, and cerium ions, can effectively kill bacteria over a long period, preventing bacterial infection at the bone defect site.

[0040] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention discloses and prepares an antibacterial hydroxyapatite fiber-gelatin composite scaffold for the first time. The composite scaffold first combines the excellent biological properties of gelatin and antibacterial hydroxyapatite, and biomimics the key structural and compositional features of cancellous bone, providing a good microenvironment for the ingrowth of new bone and blood vessels. Secondly, the antibacterial hydroxyapatite fiber is uniformly embedded in the gelatin fiber matrix, which not only effectively enhances the mechanical properties of the composite scaffold, but also endows it with good antibacterial properties. Experiments have confirmed that the composite scaffold of this invention has good antibacterial properties, biocompatibility and bone differentiation promotion properties, and has great application potential in promoting the rapid repair and regeneration of infected bone defects.

[0041] (2) The antibacterial hydroxyapatite fiber-gelatin composite scaffold disclosed in this invention is prepared by thermo-cooled phase separation and paraffin ball template leaching technology. It is composed of interwoven antibacterial hydroxyapatite fiber-gelatin composite fibers, and has regular spherical macropores and interconnected pores (each macropore ≥ 1 interconnected pore). The diameter of the composite fiber, the pore size of the spherical macropores and the porosity can be precisely controlled by controlling the phase separation temperature and the heating time of the paraffin balls.

[0042] (3) The antibacterial hydroxyapatite fiber-gelatin composite scaffold disclosed in this invention can be prepared in different specifications by adjusting the template size and the amount of antibacterial hydroxyapatite fiber / gelatin suspension injected. After simple cutting, it can be transplanted to the bone tissue repair site according to conventional methods to meet the needs of bone defects of different sizes.

[0043] In summary, the antibacterial hydroxyapatite fiber-gelatin composite scaffold disclosed in this invention is a biomedical material with great application potential in the field of bone tissue engineering. It has multiple functions, including antibacterial activity, promoting bone differentiation, and providing a favorable microenvironment for new bone and blood vessel ingrowth, and has great application potential. Attached Figure Description

[0044] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0045] Figure 1 The images show FESEM and EDS images of cerium-doped hydroxyapatite fibers and FESEM images of paraffin spheres with a particle size of 450–580 μm. In the images, ad is the FESEM image of cerium-doped hydroxyapatite fibers, e is the EDS result of the area selected in the figure, and f is an optical micrograph of the paraffin spheres. Figure 2 An optical photograph of the cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1; Figure 3The FESEM results of porous scaffolds with different compositions prepared in Examples 1, 1 and 2 are shown. Here, ac is the cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1, df is the gelatin porous scaffold prepared in Comparative Example 1, and gi is the hydroxyapatite fiber-gelatin composite scaffold prepared in Comparative Example 2. Figure 4 The XRD results are for porous scaffolds with different compositions prepared in Example 1 and Comparative Example 1, respectively. Figure 5 The mechanical properties of the stents prepared in Example 1, Comparative Example 1, and Comparative Example 2 are shown below. Figure 6 The images show FESEM images and antibacterial rate statistics of Example 1, Comparative Example 2, and the blank group after co-culturing with Staphylococcus aureus for 24 h. In the images, a represents Comparative Example 2, b represents Example 1, and c represents the antibacterial rate statistics. Figure 7 The results are FESEM (a and b) and LCSM (c) of the cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1 after co-culturing with BMSCs cells for 72 h. Among them, (b) is a further magnified FESEM result of a local area of ​​(a).

[0046] Figure 8 Micro-CT images (ac) and relative new bone formation rate (d) of rat skull defects implanted in Example 1, Comparative Example 1 and Comparative Example 2 8 weeks later. Specific implementation methods It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention is described.

[0047] Example 1: Preparation of antibacterial cerium-doped hydroxyapatite fiber-gelatin composite multi-scaffold (1) 1.5 g of paraffin balls with a diameter of 450-580 μm prepared by microemulsion method were stacked in a cylindrical mold, gently pressed to ensure full contact between the paraffin balls, and then transferred to a 37 ℃ oven for 20 min to obtain a paraffin ball template. (2) An aqueous solution containing 0.43 g CaCl2 and 0.045 g CeCl3·7H2O (dissolved in 20 mL of water), an aqueous solution containing 1.03 g NaOH (dissolved in 20 mL of water), and an aqueous solution containing 0.6 g NaH2PO4·2H2O (dissolved in 20 mL of water) were successively added dropwise to a mixed solvent consisting of 12 g oleic acid, 11 g ethanol, and 10 mL deionized water to obtain a reaction solution; (3) The reaction solution was transferred to the reaction vessel and reacted at 180 °C for 24 h to obtain a white precipitate. The white precipitate was washed three times with deionized water and anhydrous ethanol, and dried to obtain cerium-doped hydroxyapatite fibers with a Ce / (Ce+Ca) molar ratio of 3 at.%. (4) 0.2629 g of cerium-doped hydroxyapatite fiber was placed in a mixed solvent consisting of 200 mL of anhydrous ethanol and 50 mL of deionized water, and hydrothermally washed at 70 °C for 6 h. After centrifugation, the fiber was collected and then ultrasonically dispersed in a mixed solvent consisting of 10 mL of anhydrous ethanol and 10 mL of deionized water (300 W, 50 min) to obtain a cerium-doped hydroxyapatite fiber slurry with a concentration of 0.0131 g / mL. (5) Under the conditions of water bath at 45 °C and magnetic stirring for 25 min, 1.5 g of gelatin was dissolved in cerium-doped hydroxyapatite slurry to obtain a cerium-doped hydroxyapatite fiber / gelatin suspension with a gelatin concentration of 0.075 g / mL. (6) Pour 1.75 mL of the suspension onto the paraffin ball template and allow the suspension to fully fill the template under negative pressure (~900 Pa) to obtain a mixture of cerium-doped hydroxyapatite fiber / gelatin suspension and paraffin ball template. Then transfer it to an environment of -60 °C and freeze for 12 h. (7) The mixture was transferred to anhydrous ethanol at -18°C and soaked for 24 h; then transferred to 1,4-dioxane and soaked for 24 h, with fresh 1,4-dioxane replaced every 6 h, and repeated three times; then transferred to -18°C and frozen for 6 h, and finally freeze-dried at -60°C for 24 h. (8) The product obtained in step (7) was soaked in n-hexane for 16 h, and the n-hexane was replaced every 5 h, and the process was repeated three times; then it was transferred to cyclohexane for 12 h, and the cyclohexane was replaced every 4 h, and the process was repeated three times; then it was transferred to -18℃ for 6 h, and then freeze-dried at -60℃ for 24 h to obtain a non-chemically cross-linked cerium-doped hydroxyapatite fiber-gelatin composite scaffold. (9) Weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide sequentially according to the mass ratio of composite scaffold: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: N-hydroxysuccinimide in the order of 2:1:0.4. Then, measure morpholine ethanesulfonic acid buffer (0.05 mol / L, pH = 5.3) at a concentration of 0.03 wt.%. Then, dissolve the weighed 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in morpholine ethanesulfonic acid buffer to obtain a mixture. Finally, prepare a chemical cross-linking solvent according to the volume ratio of mixture to acetone of 10:90. (10) At 4 °C, the uncrosslinked composite scaffold was immersed in a chemical crosslinking solvent for 24 h for chemical crosslinking. Then, it was washed repeatedly with anhydrous ethanol and deionized water. Then, it was pre-cooled at -18 °C for 12 h and finally freeze-dried at -60 °C for 24 h to obtain cerium-doped hydroxyapatite fiber-gelatin composite multi-scaffold (cerium-doped hydroxyapatite fiber content is about 15 wt.%).

[0048] The FESEM and EDS results of the cerium-doped hydroxyapatite fiber and paraffin balls used in the preparation of the antibacterial cerium-doped hydroxyapatite fiber-gelatin composite scaffold in this embodiment are as follows: Figure 1 As shown. From Figure 1 As can be seen from a-1d, the cerium-doped hydroxyapatite fibers prepared by the solvothermal method exhibit a morphology of arbitrary-angle bending; from Figure 1 From equation e, the Ce / (Ca+Ce) molar ratio of the prepared cerium-doped hydroxyapatite fibers can be determined to be 2.88 at.%, which is close to the theoretical value; from Figure 1 As can be seen from f, the particle size of paraffin balls prepared by the microemulsion method is 480~590 μm.

[0049] The optical and FESEN images of the antibacterial cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in this embodiment are shown below. Figure 2 and Figure 3 As shown in a-3c, a large number of regular and uniform spherical pores can be observed in the scaffold, indicating that the prepared composite scaffold has high porosity; from Figure 3 As can be seen in a-3b, each spherical macropore (pore diameter 480~590 μm) contains ≥1 connecting pore (pore diameter ~100 μm); from Figure 3 As shown in Figure c, the composite fibers containing cerium-doped hydroxyapatite fibers and gelatin form an interwoven composite fiber network. The porosity, measured by the density method, is 86.5 ± 4.4%, which falls within the porosity range of human cancellous bone (75%–95%).

[0050] The FESEM and LCSM results of the antibacterial cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in this embodiment after co-culturing BMSCs cells for 72 h are as follows: Figure 7 As shown, from Figure 7 As can be seen in a and 7b, BMSCs cells spread out well on the inner wall surface of the macropores, exhibiting a polygonal shape and multiple extended pseudopodia. Figure 7 The LCSM results of c further support the FESEM results, and the above results together indicate that the prepared composite scaffold has good biocompatibility.

[0051] Example 2: Preparation of antibacterial cerium-doped hydroxyapatite fiber-gelatin composite scaffold (1) 1.5 g of paraffin balls with a diameter of 450-580 μm prepared by microemulsion method were stacked in a cylindrical mold, gently pressed to ensure full contact between the paraffin balls, and then transferred to a 37 ℃ oven for 22 min to obtain a paraffin ball template. (2) An aqueous solution containing 0.43 g CaCl2 and 0.045 g CeCl3·7H2O (dissolved in 20 mL of water), an aqueous solution containing 1.03 g NaOH (dissolved in 20 mL of water), and an aqueous solution containing 0.6 g NaH2PO4·2H2O (dissolved in 20 mL of water) were successively added dropwise to a mixed solvent consisting of 12 g oleic acid, 11 g ethanol, and 10 mL deionized water to obtain a reaction solution; (3) The reaction solution was transferred to the reaction vessel and reacted at 180 °C for 24 h to obtain a white precipitate. The white precipitate was washed three times with deionized water and anhydrous ethanol, and dried to obtain cerium-doped hydroxyapatite fibers with a Ce / (Ce+Ca) molar ratio of 3 at.%. (4) 0.4 g of cerium-doped hydroxyapatite fiber was placed in a mixed solvent consisting of 200 mL of anhydrous ethanol and 50 mL of deionized water, and hydrothermally washed at 70 °C for 6 h. After centrifugation, the fiber was collected and then ultrasonically dispersed in a mixed solvent consisting of 10 mL of anhydrous ethanol and 10 mL of deionized water (300 W, 50 min) to obtain a cerium-doped hydroxyapatite fiber slurry with a concentration of 0.02 g / mL. (5) Under the conditions of water bath at 45℃ and magnetic stirring for 25 min, 1.5 g of gelatin was dissolved in cerium-doped hydroxyapatite slurry to obtain a cerium-doped hydroxyapatite fiber / gelatin suspension with a gelatin concentration of 0.075 g / mL. (6) 1.75 mL of suspension was poured onto the paraffin ball template and the suspension was fully filled into the template under negative pressure (~900 Pa) to obtain a mixture of cerium-doped hydroxyapatite fiber / gelatin suspension and paraffin ball template. Then the mixture was transferred to an environment of -60℃ and frozen for 12 h. (7) The mixture was transferred to anhydrous ethanol at -18°C and soaked for 24 h; then transferred to 1,4-dioxane and soaked for 24 h, with fresh 1,4-dioxane replaced every 6 h, and repeated three times; then transferred to -18°C and frozen for 6 h, and finally freeze-dried at -60°C for 24 h. (8) The product obtained in step (7) was soaked in n-hexane for 16 h, and the n-hexane was replaced every 5 h, and the process was repeated three times; then it was transferred to cyclohexane for 12 h, and the cyclohexane was replaced every 4 h, and the process was repeated three times; then it was transferred to -18℃ for 6 h, and then freeze-dried at -60℃ for 24 h to obtain a non-chemically cross-linked cerium-doped hydroxyapatite fiber-gelatin composite scaffold. (9) Weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide sequentially according to the mass ratio of composite scaffold: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: N-hydroxysuccinimide in the order of 2:1:0.4. Then, measure morpholine ethanesulfonic acid buffer (0.05 mol / L, pH = 5.3) at a concentration of 0.03 wt.%. Then, dissolve the weighed 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in morpholine ethanesulfonic acid buffer to obtain a mixture. Finally, prepare a chemical cross-linking solvent according to the volume ratio of mixture to acetone of 10:90. (10) At 4°C, the uncrosslinked composite scaffold was immersed in a chemical crosslinking solvent for 24 h for chemical crosslinking. Then, it was washed repeatedly with anhydrous ethanol and deionized water. After that, it was pre-cooled at -18°C for 12 h and finally freeze-dried at -60°C for 24 h to obtain cerium-doped hydroxyapatite fiber-gelatin composite multi-scaffold (cerium-doped hydroxyapatite fiber content is about 21 wt.%).

[0052] Example 3: Preparation of antibacterial copper-doped hydroxyapatite fiber-gelatin composite scaffold (1) 1.5 g of paraffin balls with a diameter of 450-580 μm prepared by microemulsion method were stacked in a cylindrical mold, gently pressed to ensure full contact between the paraffin balls, and then transferred to a 37 ℃ oven for 20 min to obtain a paraffin ball template. (2) An aqueous solution containing 0.43 g CaCl2 and 0.027 g CuCl2·2H2O (dissolved in 20 mL of water), an aqueous solution containing 1.03 g NaOH (dissolved in 20 mL of water), and an aqueous solution containing 0.6 g NaH2PO4·2H2O (dissolved in 20 mL of water) were sequentially added dropwise to a mixed solvent consisting of 12 g oleic acid, 11 g ethanol, and 10 mL deionized water to obtain a reaction solution; (3) The reaction solution was transferred to the reaction vessel and reacted at 180 °C for 24 h to obtain a light blue-green precipitate. The light blue-green precipitate was washed three times with deionized water and anhydrous ethanol, and dried to obtain copper-doped hydroxyapatite fibers with a Cu / (Cu+Ca) molar ratio of 4 at.%. (4) 0.2629 g of copper-doped hydroxyapatite fiber was placed in a mixed solvent consisting of 200 mL of anhydrous ethanol and 50 mL of deionized water, and hydrothermally washed at 70 °C for 6 h. After centrifugation, the fiber was collected and then ultrasonically dispersed in a mixed solvent consisting of 10 mL of anhydrous ethanol and 10 mL of deionized water (300 W, 50 min) to obtain a copper-doped hydroxyapatite fiber slurry with a concentration of 0.0131 g / mL. (5) Under the conditions of water bath at 45℃ and magnetic stirring for 25 min, 1.5 g of gelatin was dissolved in copper-doped hydroxyapatite slurry to obtain a copper-doped hydroxyapatite fiber / gelatin suspension with a gelatin concentration of 0.075 g / mL. (6) Pour 1.75 mL of the suspension onto the paraffin ball template and allow the suspension to fully fill the template under negative pressure (~900 Pa) to obtain a mixture of copper-doped hydroxyapatite fiber / gelatin suspension and paraffin ball template. Then transfer it to an environment of -60℃ and freeze for 12 h. (7) The mixture was transferred to anhydrous ethanol at -18°C and soaked for 24 h; then transferred to 1,4-dioxane and soaked for 24 h, with fresh 1,4-dioxane replaced every 6 h, and repeated three times; then transferred to -18°C and frozen for 6 h, and finally freeze-dried at -60°C for 24 h. (8) The product obtained in step (7) was soaked in n-hexane for 16 h, and the n-hexane was replaced every 5 h, and the process was repeated three times; then it was transferred to cyclohexane for 12 h, and the cyclohexane was replaced every 4 h, and the process was repeated three times; then it was transferred to -18℃ for 6 h, and then freeze-dried at -60℃ for 24 h to obtain a non-chemically cross-linked cerium-doped hydroxyapatite fiber-gelatin composite scaffold. (9) Weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide sequentially according to the mass ratio of composite scaffold: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: N-hydroxysuccinimide in the order of 2:1:0.4. Then, measure morpholine ethanesulfonic acid buffer (0.05 mol / L, pH = 5.3) at a concentration of 0.03 wt.%. Then, dissolve the weighed 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in morpholine ethanesulfonic acid buffer to obtain a mixture. Finally, prepare a chemical cross-linking solvent according to the volume ratio of mixture to acetone of 10:90. (10) At 4°C, the uncrosslinked composite scaffold was immersed in a chemical crosslinking solvent for 24 h for chemical crosslinking. Then, it was washed repeatedly with anhydrous ethanol and deionized water. Then, it was pre-cooled at -18°C for 12 h and finally freeze-dried at -60°C for 24 h to obtain a copper-doped hydroxyapatite fiber-gelatin composite multi-scaffold (the content of copper-doped hydroxyapatite fiber is about 15 wt.%).

[0053] Comparative Example 1: Preparation of Gelatin Porous Scaffold (1) 2.0 g of paraffin balls with a diameter of 450-580 μm prepared by microemulsion method were stacked in a cylindrical mold, gently pressed to ensure full contact between the paraffin balls, and then transferred to a 37℃ oven for 20 min to obtain a paraffin ball template. (3) Under the conditions of water bath at 45℃ and magnetic stirring for 25 min, 1.5 g of gelatin was dissolved in a solvent consisting of 10 mL of anhydrous ethanol and 10 mL of deionized water to obtain a gelatin solution with a concentration of 0.075 g / mL. (4) Pour 1.75 mL of gelatin solution onto the paraffin ball template and allow the gelatin solution to fully fill the template under negative pressure (~1000 Pa) to obtain a paraffin ball template-gelatin solution mixture. Then transfer it to an environment of -60℃ and freeze for 12 h. (5) The mixture was transferred to anhydrous ethanol at -18°C and soaked for 24 h; then transferred to 1,4-dioxane and soaked for 24 h, with fresh 1,4-dioxane replaced every 6 h, and repeated three times; then transferred to -18°C and frozen for 6 h, and finally freeze-dried at -60°C for 24 h. (6) The product obtained in step (5) was soaked in n-hexane for 16 h, and the n-hexane was replaced every 5 h, and the process was repeated three times; then it was transferred to cyclohexane for 12 h, and the cyclohexane was replaced every 4 h, and the process was repeated three times; then it was transferred to -18℃ for 6 h and then freeze-dried at -60℃ for 24 h to obtain a non-chemically cross-linked gelatin porous scaffold. (7) Weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide sequentially according to the mass ratio of gelatin porous scaffold: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: N-hydroxysuccinimide in a ratio of 2:1:0.4. Then, measure morpholine ethanesulfonic acid buffer (0.05 mol / L, pH = 5.3) at a concentration of 0.03 wt.%. Then, dissolve the weighed 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in morpholine ethanesulfonic acid buffer to obtain a mixture. Finally, prepare a chemical crosslinking solvent according to the volume ratio of mixture to acetone of 10:90. (8) At 4°C, the uncrosslinked gelatin porous scaffold was immersed in a chemical crosslinking solvent for 24 h for chemical crosslinking. Then it was washed with anhydrous ethanol and ultrapure water in sequence, pre-cooled at -18°C for 12 h, and then freeze-dried at -60°C for 24 h to obtain the gelatin porous scaffold.

[0054] Comparative Example 2: Preparation of hydroxyapatite fiber-gelatin composite scaffold (1) An aqueous solution containing 0.44 g CaCl2 (dissolved in 20 mL of water), an aqueous solution containing 1.03 g NaOH (dissolved in 20 mL of water), and an aqueous solution containing 0.6 g NaH2PO4·2H2O (dissolved in 20 mL of water) were successively added dropwise to a mixed solvent consisting of 12 g oleic acid, 11 g ethanol, and 10 mL deionized water to obtain a reaction solution; (2) The reaction solution was transferred to a reaction vessel and reacted at 180 °C for 24 h to obtain a white precipitate. The white precipitate was washed three times with deionized water and anhydrous ethanol, and dried to obtain hydroxyapatite fiber. (3) 0.023 g of hydroxyapatite fiber was placed in a mixed solvent consisting of 200 mL of anhydrous ethanol and 50 mL of deionized water and hydrothermally washed at 70 °C for 6 h. After centrifugation, the fiber was collected and dispersed in 1.5 mL of anhydrous ethanol by ultrasonication (300 W, 50 min). Then, it was dispersed with 1.5 g of paraffin balls with a diameter of 450~580 μm prepared by microemulsion method by ultrasonication to ensure thorough mixing. The mixture was dried in a vacuum environment at 0~4 °C for 1 h to obtain a hydroxyapatite fiber / paraffin ball mixture. (4) Stack the hydroxyapatite fiber / paraffin ball mixture in a cylindrical mold, gently press it to ensure full contact of the paraffin balls, and then transfer it into a 37 ℃ oven for 45 min to obtain a hydroxyapatite fiber / paraffin ball template. (5) Under the conditions of water bath at 45℃ and magnetic stirring for 25 min, 1.5 g of gelatin was dissolved in a solvent consisting of 10 mL of anhydrous ethanol and 10 mL of ultrapure water to obtain a gelatin solution with a concentration of 0.075 g / mL. (6) 1.75 mL of gelatin solution was poured onto the hydroxyapatite fiber / paraffin ball template and the gelatin solution was fully filled into the template under negative pressure (~900 Pa) to obtain a hydroxyapatite fiber / paraffin ball template-gelatin solution mixture, and then transferred to an environment of -60℃ and frozen for 12 h. (7) The mixture was transferred to anhydrous ethanol at -18°C and soaked for 24 h; then transferred to 1,4-dioxane and soaked for 24 h, with fresh 1,4-dioxane replaced every 6 h, and repeated three times; then transferred to -18°C and frozen for 6 h, and finally freeze-dried at -60°C for 24 h. (8) The product obtained in step (7) was soaked in n-hexane for 16 h, and the n-hexane was replaced every 5 h, and the process was repeated three times; then it was transferred to cyclohexane for 12 h, and the cyclohexane was replaced every 4 h, and the process was repeated three times; then it was transferred to -18℃ for 6 h, and then freeze-dried at -60℃ for 24 h to obtain a non-chemically cross-linked strontium-doped hydroxyapatite fiber-gelatin composite scaffold. (9) Weigh 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide sequentially according to the mass ratio of composite scaffold: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: N-hydroxysuccinimide in the order of 2:1:0.4. Then, measure morpholine ethanesulfonic acid buffer (0.05 mol / L, pH = 5.3) at a concentration of 0.03 wt.%. Then, dissolve the weighed 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide in morpholine ethanesulfonic acid buffer to obtain a mixture. Finally, prepare a chemical cross-linking solvent according to the volume ratio of mixture to acetone of 10:90. (10) At 4°C, the uncrosslinked composite scaffold was immersed in a chemical crosslinking solvent for 24 h for chemical crosslinking. Then, it was washed repeatedly with anhydrous ethanol and deionized water. After that, it was pre-cooled at -18°C for 12 h and then freeze-dried at -60°C for 24 h to obtain the hydroxyapatite fiber-gelatin composite scaffold (hydroxyapatite fiber content is about 15 wt.%).

[0055] The FESEM results of porous scaffolds with different compositions prepared in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 2 As shown, from Figure 3 As can be seen from a-3i, all three types of scaffolds prepared have regular spherical macropores and interconnecting pores. The average diameter of the spherical macropores is about 500 μm, and there is ≥1 interconnecting pore within each macropore, with the interconnecting pore diameter being ~100 μm. From Figure 3 As can be seen from b and 3c, the pore wall surface and interior of the scaffold prepared in Example 1 are both composed of composite fibers consisting of cerium-doped hydroxyapatite fibers embedded in a gelatin matrix; from Figure 3 As can be seen from e and 3f, the surface and interior of the spherical pore wall of the scaffold prepared in Comparative Example 1 are both composed of gelatin fibers; from Figure 3 As shown in h and 3i, in the scaffold prepared in Comparative Example 2, hydroxyapatite fibers are concentrated on the inner surface of the spherical macropores in an attached form, while the interior of the scaffold is composed of pure gelatin fibers, with no hydroxyapatite nanofibers present. These results indicate significant differences in the composition of the three scaffolds, especially the drastically different distribution patterns of hydroxyapatite fibers in the scaffolds of Example 1 and Comparative Example 2.

[0056] The XRD results of porous scaffolds with different compositions prepared in Example 1 and Comparative Example 1 are as follows: Figure 4 As shown, the composite scaffold prepared in Example 1 is a composite phase, with gelatin as the main phase and cerium-doped hydroxyapatite as the secondary phase; the scaffold prepared in Comparative Example 1 is a pure gelatin phase.

[0057] The mechanical property test results of the antibacterial cerium-doped hydroxyapatite fiber-gelatin composite scaffold, porous gelatin scaffold, and hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1, Comparative Example 1, and Comparative Example 2 are as follows: Figure 5As shown, the Young's moduli of the three scaffolds are 8.91±0.45, 5.19±0.54, and 3.62±0.09 kPa, respectively. It can be seen that the scaffold composed of cerium-doped hydroxyapatite fibers and gelatin (i.e., Example 1) exhibits the best mechanical properties among the three scaffolds. Rigid hydroxyapatite fibers are uniformly dispersed in a flexible gelatin fiber matrix, forming a structure similar to "reinforced concrete." Under stress, the stress can be transferred from the gelatin fiber matrix to the hydroxyapatite fibers, with both materials sharing the load, thus significantly increasing the Young's modulus of the scaffold. In contrast, in the scaffold prepared in Comparative Example 2, the hydroxyapatite fibers are attached to the surface of the gelatin fibers on the inner wall of the macropores. Under stress, the stress is mainly concentrated on the gelatin fibers, and the surface hydroxyapatite is prone to detachment or breakage due to "stress concentration," failing to effectively participate in load-bearing and resulting in poor overall mechanical stability. Numerous studies have shown the crucial role of basal stiffness in regulating cell adhesion, proliferation, migration, and differentiation. In their research on osteocytes, Engler et al. found that the spreading area of ​​mesenchymal stem cells increased with increasing substrate stiffness. Therefore, the scaffold constructed in Example 1 exhibits superior stem cell adhesion and spreading properties compared to the scaffolds constructed in Comparative Examples 1 and 2.

[0058] FESEM images and statistical results of inhibition rates after co-culturing Staphylococcus aureus with Example 1, Comparative Example 2, and the blank group for 24 h are as follows: Figure 6 As shown, from Figure 6 As can be seen, the composite scaffold prepared in Example 1 has a significant antibacterial effect, with an inhibition rate of 81.35 ± 2.37%.

[0059] The Micro-CT images and relative new bone formation rates of three types of porous scaffolds prepared in Examples 1, 1, and 2 after implantation into rat skull defects for 8 weeks are shown below. Figure 8 As shown, from Figure 8 As can be seen from a and 8d, the cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1 exhibits abundant new bone formation and bridging structures that continuously cross the defect area, with a relative new bone formation rate of 49.8 ± 3.52%; while from Figure 8 As shown in Figures b-8d, the porous scaffolds prepared in Comparative Examples 1 and 2 only achieved limited bone repair, especially the pure gelatin porous scaffold prepared in Comparative Example 1, whose relative new bone formation rate was only 6.98 ± 1.43%. Studies have shown that doping with cerium, copper, and strontium ions into the interior of hydroxyapatite crystals can effectively improve its degradation performance. Therefore, the cerium-doped hydroxyapatite fiber-gelatin composite scaffold prepared in Example 1 can release Ce more quickly than the hydroxyapatite fiber-gelatin composite scaffold prepared in Comparative Example 1. 3+ / Ce 4+ Ca 2+Plasma, at low ion concentrations, recruits bone mesenchymal stem cells (BMSCs) for rapid migration to the bone defect site. As the ion concentration gradually increases, it induces BMSCs to differentiate into osteoblasts. Simultaneously, the composite scaffold of Example 1, possessing the highest Young's modulus among the three scaffolds, exhibits stiffness more conducive to stimulating the adhesion, proliferation, and differentiation of BMSCs within its scaffold. Under the combined effect of these two factors, the composite scaffold prepared in Example 1 exhibits optimal bone repair performance, thereby achieving rapid repair of bone defects.

[0060] The above description is merely a preferred embodiment of the invention and is not intended to limit the invention. Various modifications and variations can be made to the invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the invention should be included within the scope of protection of the invention.

Claims

1. An antibacterial hydroxyapatite fiber-gelatin composite scaffold, characterized in that, The composite scaffold comprises interwoven antibacterial hydroxyapatite fiber-gelatin composite fibers, and has a structural feature of regular spherical macropores and interconnected pores, with each spherical macropore containing ≥1 interconnected pore; Among them, the spherical macropores have a diameter of 200~800 μm, and the interconnected pores have a diameter of 80~120 μm; the antibacterial hydroxyapatite fiber-gelatin composite fiber has a diameter of 0.2~1.5 μm.

2. The antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 1, characterized in that, The antibacterial hydroxyapatite fiber-gelatin composite scaffold contains 10-25 wt.% antibacterial hydroxyapatite fiber.

3. The antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 1, characterized in that, The antibacterial hydroxyapatite fiber-gelatin composite scaffold also contains metal ions, which are selected from copper, silver and cerium ions, and the content of the metal ions in the hydroxyapatite fiber is 2~6 at.%.

4. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to any one of claims 1 to 3, characterized in that, First, paraffin balls are stacked and heated to obtain a paraffin ball template; antibacterial hydroxyapatite fiber is mixed with gelatin solution to prepare an antibacterial hydroxyapatite fiber / gelatin suspension; then, the antibacterial hydroxyapatite fiber / gelatin suspension is injected into the paraffin ball template under negative pressure, and an uncrosslinked composite scaffold is obtained through thermo-cooled phase separation and paraffin ball template leaching technology. Finally, an antibacterial hydroxyapatite fiber-gelatin composite scaffold was obtained through chemical cross-linking.

5. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 4, characterized in that, Includes the following steps: S1, Prepare a paraffin ball template; S2, Preparation of antibacterial hydroxyapatite fiber / gelatin suspension; S3, inject the antibacterial hydroxyapatite fiber / gelatin suspension obtained in step S2 into the paraffin ball template obtained in step S1 under negative pressure, and freeze-induced thermal phase separation. S4, the pore-forming agent paraffin is removed by pore-forming agent leaching process to obtain an unchemically cross-linked antibacterial hydroxyapatite fiber-gelatin composite scaffold. S5, the uncrosslinked antibacterial hydroxyapatite fiber-gelatin composite scaffold obtained in step S4 is chemically crosslinked, washed, pre-cooled and then freeze-dried to obtain the antibacterial hydroxyapatite-gelatin composite scaffold.

6. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 4, characterized in that, In step S1, the paraffin balls prepared by the microemulsion method are stacked and heated at 30~45℃ for 10-60 min to connect the paraffin balls to each other and form a paraffin ball template; in step S1, the preferred particle size of the paraffin balls is 400~600 μm.

7. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 4, characterized in that, Step S2 includes the following steps: S2.1, after hydrothermal cleaning, the antibacterial hydroxyapatite fiber is ultrasonically dispersed in a mixed solvent of water and ethanol to obtain an antibacterial hydroxyapatite fiber slurry with a concentration of 0.005~0.1 g / mL; S2.2, add gelatin to the slurry obtained in step S2.1, and stir at 37~50 ℃ for 10~30 min to obtain an antibacterial hydroxyapatite fiber / gelatin suspension with a gelatin concentration of 0.01~0.2 g / mL; In step S2, the antibacterial hydroxyapatite fiber is a hydroxyapatite fiber doped with antibacterial ions, wherein the antibacterial ions are selected from copper, silver and cerium ions; the antibacterial ion content is preferably 2~6 at.%.

8. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 4, characterized in that, In step S3, the antibacterial hydroxyapatite fiber / gelatin suspension obtained in step S2 is injected into the template obtained in step S1 under negative pressure and transferred to an environment of -80~-20 ℃ for freezing for 3~18 h to induce the thermal phase separation process.

9. The method for preparing the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to claim 4, characterized in that, Step S4 includes the following steps: S4.1, The product obtained in step S3 is soaked in anhydrous ethanol at -40~-10℃ for 12~36 h, and then transferred to 1,4-dioxane for 12~36 h to remove ethanol and water from the product. The product is replaced with a new 1,4-dioxane every 6~10 h. S4.2, freeze the product obtained in step S4.1 at -18±5℃ for 6~18 h and freeze-dry for 12~36 h to remove 1,4-dioxane from the product; S4.3, Soak the product obtained in step S4.2 in n-hexane for 12-36 h to completely remove the paraffin balls, and replace the n-hexane solvent with fresh solvent every 2-8 h; S4.4, The product obtained in step S4.3 is soaked in cyclohexane solution for 6-18 h to remove n-hexane, and the cyclohexane solvent is replaced every 1-6 h to obtain an uncrosslinked antibacterial hydroxyapatite fiber-gelatin composite scaffold. S4.5, Freeze the uncrosslinked composite scaffold obtained in step S4.4 at -18±5℃ for 6~18 h, and freeze-dry for 12~36 h to remove cyclohexane from the product; S4.6, prepare a chemical crosslinking solvent by mixing morpholine ethanesulfonic acid buffer containing 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide with acetone at a volume ratio of 20:80 to 5:

95. S4.7 Immerse the composite scaffold obtained in step S4.5 in the chemical crosslinking solvent obtained in step S4.6, and crosslink at 0~10℃ for 12~36 h; S4.8 The composite scaffold that has been chemically cross-linked in step S4.7 is washed, pre-cooled, and then freeze-dried to obtain a biomimetic cancellous bone antibacterial hydroxyapatite-gelatin composite scaffold.

10. The application of the antibacterial hydroxyapatite fiber-gelatin composite scaffold according to any one of claims 1 to 3 in the repair or regeneration of infected bone defects.